Experimental assessment of performance characteristics for pitching flexible propulsors. (November 2016) - Egan, Brendan C.; Brownell, Cody J.; Murray, Mark M.
Abstract: Using a flexible hydrodynamic foil that pitches to produce thrust, the most pertinent aspects of a fish-like propulsion system are replicated in a controlled environment. The pitching and flexing combination creates a hydroelastic coupling in which the fluid and flexible foil simultaneously affect each other's behavior. The project investigated relationships for the propulsors' thrust and efficiency performance to gain a better understanding of the dynamic interaction with the surrounding fluid. The analysis was conducted through reduction of the measured force and torque data. The experiments took place in a large recirculating water channel, using full span flexible propulsor models and a higher Reynolds number than previous flexible propulsor experiments. The propulsor pitched about a fixed axis at its quarter chord, with a six-axis load cell measuring the forces and torques on the shaft. The efficiency of the propulsor and the Coefficients of Thrust and Lift are presented as functions of both Strouhal Number and Stiffness Coefficient. The ensemble data will facilitate the engineering of fish-like propulsion systems for future application of this technology. Abstract : Highlights: Lift and thrust measurements are performed on pitching flexible foil propulsors for a range of flexibilities and Strouhal Numbers. Experimental data extends to higher range of Reynolds numbers than previous data. Flexibility does not give an increase in propulsive efficiency for this geometry over the parameters tested.